A critical review of experimental analyses performed on animals, post-mortem human subjects, and substitutes to explore primary blast-induced Traumatic Brain Injuries - Elster, Natacha; Boutillier, Johanna; Magnan, Pascal; Naz, Pierre; Willinger, Rémy; Deck, Caroline (Frontiers in Mechanical Engineering, 2023)
Although blast-induced Traumatic Brain Injury (bTBI) has become a signature wound of conflict, its cause is not yet fully understood. Regarding primary blast injuries i.e., those caused by the propagation of shock waves in the body, four direct and two indirect injury mechanisms have been mainly proposed in the literature. Since numerous authors have exposed instrumented animals, Post-Mortem Human Subjects (PMHS), and head substitutes to blast conditions, the aim of this review is to classify them in terms of threat, instrumentation, and investigated mechanisms. In the first part, data are collected from 6 studies on PMHS, 1 on primates, 11 on rodents, and 6 on swine for comparison purposes. Peak amplitudes of reflected pressures, intracranial pressures and cranial strains are extracted and analyzed to establish trends. Despite the small number of comparable studies, several similarities can be highlighted. Indeed, the analyses revealed a dose-response effect for most measurements. The results also depend on the orientation of the subject (forward, backward, and sideways) for the PMHS, primates, and swine. The second goal of this review is to evaluate the behavior of substitutes developed to replace PMHS experiments. Shell strains and internal pressures are thus collected on 19 geometric and anthropomorphic substitutes to assess whether they faithfully represent a human head. The results showed that these substitutes are for the most part not properly designed and therefore cannot yet reliably replace PMHS experimental data.